Development of NbN based Kinetic Inductance Detectors on sapphire and diamond substrates for fusion plasma polarimetric diagnostics - Mazzocchi, Francesco (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
This work aimed at designing, studying and producing the first prototypes of KIDs tailored for fusion plasma polarimetric diagnostics. Diamond was considered for the first time as substrate material for low-temperature superconducting detectors given its unmatched optical, radiation hardness and thermal qualities, properties necessary for working environments potentially saturated with radiation. This work represents a first step toward the optimization and final application of this technology.